Pelatihan Teknik Ecoprint Sebagai Upaya Peningkatan Keterampilan Kelompok PKK Desa Janti Waru Sidoarjo - Hamzah, Yayu Sriwahyuni; Safitri, Feby Salma Ayu; Priambodo, Sebastianus; Ikhwanuddin, Ikhwanuddin; Dzinnur, Cilda Tesisa Ilmawan; Judiono, Judiono; Djaelani, M. (Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the skills of PKK members in Janti Waru Village, Sidoarjo through ecoprint technique training as a form of community empowerment based on local potential. The training adopted the Asset-Based Community Development (ABCD) approach, focusing on utilizing community-owned assets such as natural materials from the surrounding environment. The training was conducted through several stages: preparation, material delivery, hands-on practice, and evaluation. Questionnaire results showed that 90% of participants strongly agreed that the training improved their skills, 65% stated that the materials were clearly delivered, and 95% of participants expressed interest in ecoprint techniques. However, only 50% of participants indicated readiness to develop ecoprint-based businesses. These findings suggest that while the training was effective in enhancing skills and interest, further mentoring is needed to encourage the establishment of independent businesses. Overall, this activity has made a positive contribution to women’s empowerment and the sustainable development of local economic potential.